2022
DOI: 10.3390/jcm11185394
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of COVID-19 on the Perioperative Course of Acute Coronary Syndrome in Poland: The Estimation of Perioperative Prognosis and Neural Network Analysis in 243,515 Cases from 2020 to 2021

Abstract: COVID-19 causes thromboembolic complications that affect the patient’s prognosis. COVID‑19 vaccines significantly improve the prognosis for the course of the infection. The aim of this study was to evaluate the impacts of patient characteristics, including COVID-19 vaccinations, on perioperative mortality in acute coronary syndrome in Poland during the pandemic. We analyzed the data of 243,515 patients from the National Registry of Invasive Cardiology Procedures (Ogólnopolski Rejestr Procedur Kardiologii Inwaz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…An international registry among 3011 hospitalised COVID-19 patients reported cardiac incidence of 11.6% (acute coronary syndrome; 0.5%, type II cardiac ischaemia; 0.8%, heart failure; 1.8% and arrhythmia/conduction disorders; 8.6%) and pulmonary embolism; 6.6% 14. On the other hand, a neural network study using Polish National Registry of Invasive Cardiology Procedures reported that the COVID-19 infection had not affected periprocedural death in acute coronary syndrome and concluded that the evaluation of classic clinical risk factors is also important during the COVID-19 pandemic 15…”
Section: Discussionmentioning
confidence: 99%
“…An international registry among 3011 hospitalised COVID-19 patients reported cardiac incidence of 11.6% (acute coronary syndrome; 0.5%, type II cardiac ischaemia; 0.8%, heart failure; 1.8% and arrhythmia/conduction disorders; 8.6%) and pulmonary embolism; 6.6% 14. On the other hand, a neural network study using Polish National Registry of Invasive Cardiology Procedures reported that the COVID-19 infection had not affected periprocedural death in acute coronary syndrome and concluded that the evaluation of classic clinical risk factors is also important during the COVID-19 pandemic 15…”
Section: Discussionmentioning
confidence: 99%
“…In a neural network model analysis of data collected from 161 catheterization laboratories in Poland throughout the year 2021, the most crucial variable for the prognosis of STEMI patients was the time from first medical contact to balloon inflation [ 18 ]. In the present study, there was no statistically significant difference between groups as regards the door-to-balloon or the total ischemic time.…”
Section: Discussionmentioning
confidence: 99%
“…Patients from the pre-vaccination period were analyzed to eliminate the effect of vaccination on the studied parameters. A study of patients with ACS and the impact of vaccination was presented by our research team in another paper [ 26 ]. Correlations between acute coronary syndromes and various clinical, peri-procedural, and environmental factors have been studied by our team for several years [ 15 , 27 , 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…Air pollution data obtained from the Main Environmental Protection Inspectorate were analyzed. Air pollutants recorded in 66 air monitoring stations in Poland were analyzed for their content of PM10, PM2.5, and heavy metals such as lead (Pb), nickel (Ni), cadmium (Cd) and arsenic (As) [ 26 ]. Daily data for each analyzed pollutant were obtained from the Chief Inspectorate of Environmental Protection for 66 stations in 16 provinces in Poland.…”
Section: Methodsmentioning
confidence: 99%